Promotion and Optimal Retirement - Stern, Steven (Journal of Labor Economics, 1987)
In this paper, a firm maximizes profits over choices of wage schedules and hiring schedules in a model with (1) turnover costs, (2) a productivity function that depends on position and experience, and (3) employee utility functions that depend on monetary compensation and position. It is shown that firms may have reason to encourage employees to retire before their reservation wage is greater than their marginal product. However, if an alternative definition of marginal product is used, the usual relation holds.